Genetic and morphological evidence for a new species of the Maculatus Group of Anopheles subgenus Cellia (Diptera: Culicidae) in Java, Indonesia - Rusdiyah Sudirman Made Ali (2019)
© 2019 The Author(s). Background: Anopheles maculatus, a species of the Maculatus Group of subgenus Cellia (Diptera: Culicidae), is an important vector of human malarial protozoa in Java, Indonesia. However, the identity of this species in Indonesia has been questionable because published reports and records are based mainly on morphological identification, which is unreliable for distinguishing members of the Maculatus Group due to overlapping characters. Methods: We performed morphological assessments, metaphase karyotype preparations, phylogenetic analyses of ITS2 and cox2 sequence data and cross-mating experiments to determine whether the Javanese form and An. maculatus (s.s.) from Thailand were conspecific. Results: The adults of the Java strain are similar to those of An. maculatus (s.s.), but the larvae and pupae exhibit significant differences. The metaphase karyotype of Javanese specimens includes a long acrocentric X chromosome and a small telocentric Y chromosome, which are distinct from other members of the Maculatus Group. Cross-mating of the Java strain with An. maculatus (s.s.) revealed genetic incompatibility. Phylogenetic analysis of ITS2 and cox2 sequences revealed that the Java strain forms a single clade that is distinct from clades of other members of the group (Kimura 2-parameter, K2P, genetic distances 3.1-19.2% and 1.6-9.6%, respectively). Conclusions: This study provides evidence that the Javanese form of An. maculatus is not conspecific with An. maculatus (s.s.) and constitutes a previously unrecognized species of the Maculatus Group.